Health insurance of rural/township schoolchildren in Pinggu, Beijing: coverage rate, determinants, disparities, and sustainability - Zhu Yiliang; Zhu Jane M; Liu Rui (International Journal for Equity in Health, 2008)
Abstract Background As China re-establishes its health insurance system through various cooperative schemes, little is known about schoolchildren's health insurance. This paper reports findings from a study that examined schoolchildren's insurance coverage, disparities between farmer and non-farmer households, and effects of low-premium cooperative schemes on healthcare access and utilization. It also discusses barriers to sustainable enrollment and program growth. Method A survey of elementary school students was conducted in Pinggu, a rural/suburban district of Beijing. Statistical analyses of association and adjusted odds ratio via logistic regression were conducted to examine various aspects of health insurance. Results Children's health insurance coverage rose to 54% by 2005, the rates are comparable for farmers' and non-farmer's children. However, 76% of insured farmers' children were covered under a low-premium scheme protecting only major medical events, compared to 42% among insured non-farmers' children. The low-premium schemes improved parental perceptions of children's access to and affordability of healthcare, their healthcare-seeking behaviors, and overall satisfaction with healthcare, but had little impact on utilization of outpatient care. Conclusion Enrolling and retaining schoolchildren in health insurance are threatened by the limited tangible value for routine care and low reimbursement rate for major medical events under the low-premium cooperative schemes. Coverage rates may be improved by offering complimentary and supplementary benefit options with flexible premiums via a multi-tier system consisting of national, regional, and commercial programs. Health insurance education by means of community outreach can reinforce positive parental perceptions, hence promoting and retaining insurance enrollment in short-term.